2015
DOI: 10.1091/mbc.e14-08-1307
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-dependent entry and vesicle-mediated exocytosis define insulin transcytosis across microvascular endothelial cells

Abstract: How insulin traverses the continuous endothelium of the microvasculature has been poorly studied. Development of a novel assay to measure insulin transcytosis reveals an unexpected role for clathrin in insulin transendothelial transport. Insulin transcytosis is dynamin and clathrin dependent but does not require cholesterol or caveolin-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 40 publications
1
83
0
1
Order By: Relevance
“…The phenotypic contrast between microvascular and macrovascular ECs (34) creates difficulties in interpretation. In fact, the mechanism by which insulin is taken up by ECs depends on the type of EC used (35). who previously showed that the delivery of insulin to SkM is not saturable in dogs (12).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic contrast between microvascular and macrovascular ECs (34) creates difficulties in interpretation. In fact, the mechanism by which insulin is taken up by ECs depends on the type of EC used (35). who previously showed that the delivery of insulin to SkM is not saturable in dogs (12).…”
Section: Discussionmentioning
confidence: 99%
“…For the staining of viral nucleoprotein and PECAM-1, antigen retrieval was performed by boiling for 15 min in citric acid buffer, cooling for 45 min, and then blocking and permeabilization. Lung sections were stained with rabbit anti-PECAM-1 (1:500) overnight and with mouse anti-influenza NP (1:75) for 1 h. The colocalization of viral NP and PECAM-1 was quantified using Manders' coefficient (27) as determined using Volocity software.…”
Section: Methodsmentioning
confidence: 99%
“…Transcytosis of albumin was detected using total internal reflection fluorescence microscopy, as recently described (28). Briefly, rhodamine-albumin (Sigma-Aldrich) was allowed to bind to the apical membrane at 4°C for 10 min, after which excess albumin was washed off.…”
Section: Albumin Transcytosis Assaymentioning
confidence: 99%